Subcutaneous Cavernous Hemangioma in the Nasal Dorsum: Report of Case Treated with Endoscopic Rhinoplasty - Socher,Jan Alessandro (2014)
Introduction Hemangiomas are vascular malformations, with slow blood flow, that can occur in any part on the body. They are more common in women and, predominantly, are isolated lesions. The malformation does not spontaneously regress. Subcutaneous hemangioma is a rare variant with an aggressive growth pattern that sometimes recurs after excision. Objective Case report of a subcutaneous cavernous hemangioma in the nasal dorsum treated with endoscopic rhinoplasty. Case Report A 27-year-old woman had a fibroelastic tumor mass in the midline of the nasal dorsum, which was pulsatile; she had obstruction and nasal congestion with associated rhinorrhea, with evolution and worsening over the previous 2 years. Computed tomography showed a tumor demarcated in the nasal dorsum without evidence of intracranial communication. Endoscopic rhinoplasty with septoplasty and associated paranasal sinus sinusectomy was performed without arteriography embolization, sclerotherapy, or laser. Pathologic diagnosis showed cavernous hemangioma. Postoperative follow-up shows no recurrence at 3 years. Discussion This case presented with atypical features, thus making the diagnosis a challenge. Imaging studies were required to confirm the vascular nature of the tumor. Excisional biopsy is the procedure of choice for pathologic examination. Subcutaneous hemangiomas never involute and always need treatment. The surgical approach is exceptional because there was no preoperative diagnosis. In addition, the closed technique provided best aesthetic results in this case. Conclusion Endoscopic rhinoplasty is suitable for nasal dorsum tumor resection and has superior aesthetic result to open techniques.